Poor menstrual management facilities in the work place, a major challenge experienced by working women: a cross sectional pilot study conducted in Kerala - Koshy, Manju; Khadir, Fezeena; Cheriyan, Sumina; Kumari, Bindu (International Journal Of Community Medicine And Public Health, 2025)
Background: Secrecy and stigma around menstruation hinder effective menstrual hygiene management (MHM) in emergencies, causing distress, discomfort, and barriers to education, employment, and social well-being while increasing health risks. The main objective of the study is to identify the adequacy of facilities provided in the workplace for menstrual management. This study also attempts to assess the efficacy of supportive environment conducive for a menstruating woman (including menstrual products disposal) and subsequent distress associated in the workplace. Methods: The study participants were all educated and employed women of menstruating age between 18-45 years, either working in private/ government organizations/ self-employed sectors in Kerala. Primary data was collected from 232 working women of Kerala using structured self-administered questionnaire enquiring about the sanitation and hygiene facilities. General health questionnaire (GHQ-12) was used to assess the severity of any mental discomfort at the onset of menstruation and during menstruation. Results: The study revealed critical issues: 62.3% of women struggled with menstrual product disposal due to inadequate workplace facilities, 50.2% faced physical or mental discomfort from poor hygiene practices, and 71% reported a lack of menstrual management aids at work. Conclusions: Workplace menstrual hygiene impacts women's well-being, attendance, and productivity but is often overlooked. Reliable empirical evidence on menstrual health remains limited.